Islamic Parties, the 1955 Elections, and Center-Regional Relations: The West Sumatran Experience - Israr; Zeffry; Yudhi Andoni (Islam Realitas: Journal of Islamic and Social Studies, 2025)
This article examines the role of Islamic parties in West Sumatra concerning central-regional relations before and after the 1955 General Election, specifically during the 1950s. The historical study reveals that political landscape in Central Sumatra after the 1955 General Elections was non-linear.  Central Sematra was dominated by Islamic parties, especiallly Masyumi Party,  in contrast to the national election results, whichwere won by secular parties, especially the PNI. This discrepancy significantly impacted the escalation of conflict between the region and the central political authorities.  This central-regional conflict culminated in the PRRI rebellion between 1958 and 1961 which was not only contributed to the decline of Islamic parties but also reshaped  the historical narrative concerning the role of the Minangkabau ethnic group in Indonesia.